Meningkatkan Prestasi Belajar Siswa Tunagrahita Melalui Media Flashcard Pada Pelajaran IPA Di SLB Swasta Melati Ceria - Miludwi Lestari (Guruku: Jurnal Pendidikan dan Sosial Humaniora, 2023)
Mentally retarded students have obstacles in the intelligence aspect, namely they have Mentally retarded students have obstacles in the intelligence aspect, namely they have an IQ level that is more than average. This has an impact on low academic achievement, especially in science subjects regarding body parts and how to care for them. This research aims to improve the learning achievement of mentally retarded students in science lessons, especially body parts and how to care for them using flashcard learning media. This research was carried out at the Melati Ceria Private SLB. This research uses a classroom action research method with two learning cycles. Students with intellectual disabilities in class 1 at SDLB level were the subjects of this research. Test techniques and analysis using simple descriptive statistical analysis are the methods for collecting data in this research. The conclusion of this research shows that there is an increase in science learning achievement using flashcard media for mentally retarded students in class 1 of SLB Swasra Melati Ceria.